Economic Evaluation of the Integration of Local Plant Resources and Goats in Central Lombok - Amalyadi, Rezki; Karni, Ine; Aminurrahman, Aminurrahman; Septian, I Gede Nano; Sulistiani, Baiq (Bulletin of Applied Animal Research, 2025)
This study aims to analyze the financial feasibility of goat farming businesses in Central Lombok Regency based on biological and economic parameters. The research data was obtained through a questionnaire survey conducted on 30 goat farmers using purposive sampling. The collected data were then analyzed using a financial approach through Net Present Value (NPV), Benefit-Cost Ratio (BCR), and Internal Rate of Return (IRR). Furthermore, three business scenarios were tested, namely: (1) baseline conditions, (2) a 20% increase in the initial population, and (3) the application of feed preservation technology. The results showed that all scenarios had a negative NPV and BCR < 1 at a discount rate of 10%, indicating that the business is not yet financially viable under current conditions. Sensitivity analysis indicates that feed technology has the potential to improve viability if accompanied by a reduction in investment costs or higher productivity. A reduction in the offtake rate to 10–15% and a strategy to increase selling prices are recommended to maintain population sustainability and profitability. These findings provide input for policymakers and business actors in developing competitive goat businesses. Keywords: financial analysis, BCR, IRR, goat, Central Lombok, NPV.